Cinnamaldehyde is a biologically active compound for the disinfection of removable denture: blinded randomized crossover clinical study - Marco Antônio Lavorato de Almeida; André Ulisses Dantas Batista; Maria Rejane Cruz de Araújo; Vanessa Fabiana Dei Santi de Almeida; Paulo Rogério Ferreti Bonan; Danielle Nóbrega Alves; Tereza Karla Vieira Lopes da Costa; Diego Figueiredo Nóbrega; Ricardo Dias de Castro (BMC, 2020)
Abstract Background Fungal infections associated with the use of dentures, like denture stomatitis, are difficult to prevent and treat. This in situ study aimed to investigate the efficacy of cinnamaldehyde for the disinfection of complete removable dentures, and the effect on the physical and mechanical properties (Vickers microhardness, color, and surface roughness) of the acrylic resin. Methods Acrylic resin disks were inserted into the dentures of a probabilistic sample of 33 complete denture users, that used cinnamaldehyde (27 μg/mL) and 0.5% sodium hypochlorite solutions in a 20 min/7-days protocol of dentures immersion in each solution, with a wash-out period of 7 days, to constitute a crossover-study. The disks were analyzed before and after the immersion, for the presence of microorganisms (CFU/mL) and by scanning electron microscope (SEM). Also, the surface roughness (Ra) and Vickers microhardness were measured, and color parameters were analyzed using the National Bureau of Standards (NBS) method. Data was analyzed by Wilcoxon and Friedman (microbiological evaluation), paired t-test (color and roughness) and independent t-test (Vickers hardness) (α = 0.05). Results A significant reduction (P < 0.05) in the number of microorganisms was observed for each species (total microorganisms, Streptococcus mutans, and Candida spp.), with no significant differences (P > 0.05) between hypochlorite and cinnamaldehyde. There was an increase in the roughness and a decrease in the hardness of the test specimens, with no difference between the two disinfectant substances (P > 0.05). Both hypochlorite and cinnamaldehyde also caused changes in color, considered as "perceptible" by the NBS classification, but with no significant difference between disinfectant substances (P < 0.05), and under the clinically acceptable limit (ΔE ≤ 3.7). Conclusion The 27 μg/mL cinnamaldehyde solution was effective against all evaluated microorganisms and caused minor alterations in hardness, surface roughness, and color parameters, with no clinical relevance.